Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/0307174x1704400208
|View full text |Cite
|
Sign up to set email alerts
|

The Physicomechanical and Rheological Characteristics of Wood–polymer Composites Based on Thermally and Mechanically Modified Filler

Abstract: The effect of different wood fillers on the physicomechanical and rheological properties of wood–polymer composites was studied. It was shown that thermal and mechanochemical modification of wood flour has a considerable effect on the properties of wood–polymer composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
0
0
2
Order By: Relevance
“…However, when obtaining polymer composites filled with natural fillers, the problem of the compatibility of the hydrophobic matrix and hydrophilic fillers arises. In this way, it is becoming important to study the modification of such polymer composites in order to improve the compatibility of components [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when obtaining polymer composites filled with natural fillers, the problem of the compatibility of the hydrophobic matrix and hydrophilic fillers arises. In this way, it is becoming important to study the modification of such polymer composites in order to improve the compatibility of components [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are also various methods of plasma surface modification for polyolefins [ 12 , 13 ], which, while expensive, is an environmentally friendly and versatile method. In the articles [ 5 , 14 ], the authors presented a review of thermo-modification as a method for improving the surface properties of polymers, especially polyolefins. This modification allows for improved wettability and adhesion properties of polyolefin surfaces, especially for composites filled with natural fillers.…”
Section: Introductionmentioning
confidence: 99%
“…However, using smaller particles resulted in higher heat deflection temperature (HDT) values. Volfson et al [25] found that torrefied pine filler in a 50% wood-to-polypropylene ratio improved the tensile strength by 38% and reduced the elongation at the break by 12%.…”
Section: Introductionmentioning
confidence: 99%
“…Существуют различные химические или физические методы модификации полимерных композитов с растительными наполнителями [6][7][8][9][10][11][12][13][14]. В работе [6] показано, что термо-и механо-химическая модификация древесной муки оказывает существенное влияние на свойства полимерных композитов.…”
Section: Introductionunclassified
“…Существуют различные химические или физические методы модификации полимерных композитов с растительными наполнителями [6][7][8][9][10][11][12][13][14]. В работе [6] показано, что термо-и механо-химическая модификация древесной муки оказывает существенное влияние на свойства полимерных композитов. В работах [7][8][9] используют физические методы модификации, относящиеся к экспонированию полимерных композитов под действием излучений различной природы: радиоволн, ультрафиолета, потоков заряженных частиц.…”
Section: Introductionunclassified